Inclusion of elderly or frail patients in randomized controlled trials of targeted therapies for the treatment of metastatic colorectal cancer: A systematic review. Issue 1 (January 2018) - Gouverneur, Amandine; Salvo, Francesco; Berdaï, Driss; Moore, Nicholas; Fourrier-Réglat, Annie; Noize, Pernelle
Abstract: Treatment of metastatic colorectal cancer (mCRC) has been modified since the launching of targeted therapies. Colorectal cancer (CRC) is common in elderly patients; their representation in randomized controlled trials (RCTs) is thus crucial. This study aimed to evaluate and quantify the inclusion of elderly/frail patients in RCTs of targeted therapies in mCRC. A systematic review using Medline, Scopus, Cochrane Database and ISI Web of Science was performed to identify all phase II/III RCTs of bevacizumab, cetuximab, panitumumab, regorafenib and aflibercept in mCRC until January 2015. Two reviewers independently performed studies selection, and data extraction. The protocol was registered in Prospero (CRD42015016163). Among 1, 369, identified publications, 54 RCTs were selected. Nine RCTs (17%) excluded elderly patients; median age of the included population was < 65 years old in 50 RCTs (93%). Twenty RCTs (37%) excluded frail patients, and many RCTs excluded patients with uncontrolled hypertension or heart failure, patients treated with specific drugs (mainly anticoagulants), and patients with inadequate creatinine clearance. Elderly/frail patients are underrepresented in RCTs studying targeted therapies in mCRC, and those elderly patients included in RCTs do not reflect well the general elderly population with mCRC because of the exclusion criteria. RCTs results concerning targeted therapies can be inferred only to relatively healthy elderly subjects.